What is a 'competitive return' to a landowner? Parkhurst Road and the new UK planning policy environment. Issue 4 (2nd October 2019) - Crosby, Neil; Wyatt, Peter
ABSTRACT: In the UK, contributions from landowners towards the provision of affordable housing are obtained through a process of negotiation that centres on the financial viability of each development proposal. National Planning Practice Guidance, first published in 2014 and recently revised in 2018 and 2019, provides the Government framework for these negotiations and sets parameters for the financial viability appraisals. Failure to achieve levels of affordable housing set out in local plans has been attributed to 'gaming' strategies employed by landowners and developers within viability negotiations. This paper examines how planning guidance has influenced financial viability appraisals. A key issue within these appraisals is the determination of a suitable return to the landowner, known as Benchmark Land Value. Using a case study approach to investigate two planning appeals and a subsequent High Court decision concerning a residential development site in London, this paper demonstrates how planning policy and practice guidance on viability can lead to reduced planning obligations being delivered. It identifies the technical concerns that need to be addressed to enable appraisals to determine land prices that are fair to landowners, whilst delivering policy-compliant levels of affordable housing, and discusses whether the revised National Planning Guidance has made those changes.